Acute appendicitis secondary to metastatic uterine cervix squamous cell carcinoma. Case report - Parra Medina, Rafael; López-Correa, Patricia; Pacheco, Marwil; Romero Rojas, Alfredo Ernesto (Revista Colombiana de Cancerología, 2023)
Primary and secondary neoplasms of the appendix are rare and found in approximately 1% of surgical appendectomy specimens. Cervical squamous cell carcinoma (CSCC) spreads mainly by direct local invasion of adjacent tissues and lymphatics and, less commonly, through blood vessels. The spread of CSCC via lymphatics occurs early and is present in 25-50% of patients with stage IB and II carcinomas. We present a 31-year-old female with a history of stage IVB CSCC. The patient received palliative radiotherapy (3 Gy divided for a total of 30 Gy) and later chemotherapy (cisplatin 50 mg/m2 IV and paclitaxel 175 mg/m2 IV). Two months after the onset of therapy with radiotherapy and chemotherapy, she was admitted to the hospital, presenting with abdominal pain, fever, and vomiting. Laparotomy revealed perforated appendicitis and an intra-abdominal abscess with no evidence of ovary or fallopian tube compromise. Histopathological examination of the excised specimen evidenced a severe acute inflammatory process and the presence of CSCC. In summary, we describe the second case of acute appendicitis secondary to metastatic CSCC, published in the medical literature. This is an interesting case due to the rarity of acute appendicitis associated with metastatic cervical cancer in the appendix via lymphatic vessels. The history of CSCC played a significant role in defining the histopathological diagnosis.